Epimerization of C5 of an N-hydroxypyrrolidine in the synthesis of swainsonine related iminosugars. Issue 19 (19th April 2016) - Qian, Bao-Chen; Kamori, Akiko; Kinami, Kyoko; Kato, Atsushi; Li, Yi-Xian; Fleet, George W. J.; Yu, Chu-Yi
Abstract : Swainsonine, 8a- epi -swainsonine and related compounds were synthesized via a flexible route from cyclic nitrone and assayed against various glycosidases. Abstract : Epimerization of C5 of an N -hydroxypyrrolidine ring by regioselective oxidation to a nitrone followed by diastereoselective reduction provides a new approach to the synthesis of swainsonine and related compounds. The only protection in the synthesis of the potent mannosidase inhibitor DIM (1, 4-dideoxy-1, 4-imino-d -mannitol) was the acetonation ofd -mannose.